(untitled) (Bulletin of the International Association for Paleodontology, 2022)
Dental anomalies are rare developmental alterations involving the normal number, morphology, size, eruption, and position of teeth. Although the etiology of these anomalies is not clear, since they are caused by interactions between genetic, epigenetic, and environmental factors, heredity plays an important role in their onset. Aims: The present study reports two new archaeological cases of dental anomalies in number and position from Prehistoric Eastern Sudan. Materials and methods: The cases reported relate to two individuals from the Mesolithic site UA50, in the region of Kassala, Eastern Sudan. The description and differential diagnosis of the anomalies were performed by morphological analysis and, in one case, radiographic observation. Results: An adult male shows mandibular supernumerary premolars, erupted on the lingual side, between the second premolar and the first molar. The anomaly is bilateral and the additional teeth have independent roots and resemble permanent premolars in both morphology and size. In a young adult female the agenesis of both mandibular central incisors was recorded, coupled with both mandibular canines impaction and the transmigration of the right one. The transmigrated canine has moved to the place left empty by the central incisors, where it has erupted vertically. The retention of the mandibular right deciduous canine was observed. Conclusion: Since the evidence of dental anomalies from past populations is still scarce, the cases observed will increase the known archaeological literature. Moreover, as far as we know, the cases reported are the oldest documented cases of dental anomalies recorded in a Sudanese archaeological population.